Montenegro - Debt Sustainability Analysis - World Bank (Washington, DC, 2013)
This report assesses Montenegro's public and external debt sustainability under alternative scenarios. The baseline scenario assumes continued implementation of a macroeconomic stabilization and structural reform program, while the low case scenario describes the alternative of a sluggish growth environment due to policy slippage/weak reform. In addition, other sensitivity tests are conducted in order to highlight the vulnerability of the baseline case to specific shocks. The report concludes that Montenegro's public debt would be highly sustainable if economic reforms continue at their current pace, and the 2007 fiscal policy is maintained over the coming years.